Improved Quantification of Cell Density in the Arterial Wall—A Novel Nucleus Splitting Approach Applied to 3D Two-Photon Laser-Scanning Microscopy - van der Laan, Koen W. F.; Reesink, Koen D.; van der Bruggen, Myrthe M.; Jaminon, Armand M. G.; Schurgers, Leon J.; Megens, Remco T. A.; Huberts, Wouter; Delhaas, Tammo; Spronck, Bart (Frontiers in Physiology, 2022)
Accurate information on vascular smooth muscle cell (VSMC) content, orientation, and distribution in blood vessels is indispensable to increase understanding of arterial remodelling and to improve modelling of vascular biomechanics. We have previously proposed an analysis method to automatically characterise VSMC orientation and transmural distribution in murine carotid arteries under well-controlled biomechanical conditions. However, coincident nuclei, erroneously detected as one large nucleus, were excluded from the analysis, hampering accurate VSMC content characterisation and distorting transmural distributions. In the present study, therefore, we aim to 1) improve the previous method by adding a “nucleus splitting” procedure to split coinciding nuclei, 2) evaluate the accuracy of this novel method, and 3) test this method in a mouse model of VSMC apoptosis. After euthanasia, carotid arteries from SM22a-hDTR Apoe-/- and control Apoe-/- mice were bluntly dissected, excised, mounted in a biaxial biomechanical tester and brought to in vivo axial stretch and a pressure of 100 mmHg. Nuclei and elastin fibres were then stained using Syto-41 and Eosin-Y, respectively, and imaged using 3D two-photon laser scanning microscopy. Nuclei were segmented from images and coincident nuclei were split. The nucleus splitting procedure determines the likelihood that voxel pairs within coincident nuclei belong to the same nucleus and utilizes these likelihoods to identify individual nuclei using spectral clustering. Manual nucleus counts were used as a reference to assess the performance of our splitting procedure. Before and after splitting, automatic nucleus counts differed -26.6±9.90% (p<0.001) and -1.44±7.05% (p=0.467) from the manual reference, respectively. Whereas the slope of the relative difference between the manual and automated counts with regard to the manual count was significantly negative before splitting (p=0.008), this slope became insignificant after splitting (p=0.653). Smooth muscle apoptosis led to a 33.7% decrease in VSMC density (p=0.008). Nucleus splitting improves the accuracy of automated cell content quantification in murine carotid arteries and overcomes the progressively worsening problem of coincident nuclei with increasing cell content in vessels. The presented image analysis framework provides a robust tool to quantify cell content, orientation, shape, and distribution in vessels to inform experimental and advanced computational studies on vascular structure and function.